Gait Transition Speed and the Aerobic Thresholds for Walking and Running in Women - Davor Sentija; Vesna Babic; Lucija Kolic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Recently, it has been shown that the preferred transition speed between walking and running (PTS) in men does not differ from the aerobic thresholds (AT) for both walking (ATw) and running (ATr). The PTS in men was also found to be related to ATr, but not for ATw (Sentija & Markovic, 2009). No study has, to the best of our knowledge, examined these relationships in female subjects. Men and women show no significant gender differences in the gait transition speed, although women have a lower aerobic capacity (VO2max) than men do. Therefore, the present study aimed to explore the relationship between ATw, ATr, and the PTS in young, healthy women. Eleven female PE students (19.5+/-0.5y, 169.4+/-5.7cm) performed five treadmill tests: 1) to determine the individual PTS, 2-3) two fast ramp treadmill tests, running in one (VO2max test) and walking in the other, 4-5) two incremental tests with 4-min stages, walking in one and running in the other, in order to determine steady-state VO2 at speeds below and above PTS (5-9 km/h). The AT in ramp tests were determined from gas exchange data (V-slope method). The ATr was similar (7.34+/-0.52 km/h) to PTS (7.21+/-0.27 km/h, p>.05), while ATw was significantly lower (6.64+/-0.47 km/h, p<.001). The PTS was significantly correlated with both ATr (r=0.77) and ATw (r=0.72). A high correlation was also present between ATr and ATw (r=0.80). Several findings in our study suggest significant gender differences in the PTS/AT relationship: 1) the ATw in female subjects was found to be significantly lower than both the ATr and PTS, suggesting that the speed at the aerobic threshold in women depends on the modality of gait, and 2) the ATw was significantly correlated to both, PTS and ATr suggesting that the ATw could also be a significant predictor of the PTS in young women. Our results indicate that the PTS and the AT in young women are similar to the values reported for young men. In young women, the PTS is highly related to ATr and, to a lesser degree, with the aerobic threshold for walking. Gender differences should be taken into consideration for the proper interpretation of the factors that determine the gait transition speed between walking and running.